Study of Biological Effect of CHO-Cell Elongating Factor of Vibrio cholerae on Models in vitro and in vivo - E. V. Monakhova; G. M. Fedorenko; A. B. Mazrukho; R. V. Pisanov; V. D. Kruglikov; O. V. Markina; L. P. Alekseeva (Проблемы особо опасных инфекций, 2012)
Studied were morphological, physiological and ultrastructural changes in the cell culture L-929 and in the intestine of suckling mice in the presence of Cef (CHO cell elongating factor) of Vibrio cholerae. Registered were cellular elongation, cytoplasm vacuolization, an increase in the number of lysosomes, retraction and nuclei deformation in the L-929 cell culture. Statistical significance test confirmed that in vivo Cef caused the accumulation of fluid in suckling mice. Electron microscopy of the epithelial cells of small intestine revealed vacuolization and myelin-like structures formation in cytoplasm and nuclei, swelling of mitochondria, clarification of their matrix and destruction of cristae. Cristae were filled with mucus. The involvement of mast cells caused the increasing of capillary permeability which enhanced dehydration. These changes confirmed Cef participation in manifestation of Vibrio cholerae pathogenic properties.